GLOBALNA ELITA – PRÓBA ANALIZY POJĘCIA NA PRZYKŁADZIE POLSKICH STUDENTÓW - Łuczak, Marta (Studia Europaea Gnesnensia, 2018)
This paper aims to answer the question whether use of the designation of “global elite” to describe persons experiencing multiple migrations is theoretically justified. The author analyzes the situation on the examples of Polish students who study at universities abroad. Being in a privileged position among other migrants, students may be perceived as people aspiring to membership in the international community. The author discusses the attributes indicating their elite status and traits which makes use of the term doubtful if employed with regards to persons who repeatedly change their country of residence.